Expressing eMotions Through Participation in Painting - Molly Bathje MS, OTR/L (Scholarworks @ WMU, 2013)
The cover of the Winter 2013 Open Journal of Occupational Therapy, titled Miles eMOTION, was created by Miles Scharfenberg, an 18-year-old young man with multiple developmental impairments. Miles' story and his artwork provide a reflection on the ways in which creativity and art can enhance the lives of people with disabilities and their families. Miles' art exists because of his drive toward engagement and participation in life, but also essential is his mother's commitment to providing opportunities for him to be creative. The Miles eMOTION series of paintings can inspire occupational therapists, families, caregivers, and people with disabilities to incorporate art making as a part of their occupational profile